The Antibacterial Activity of Thymol Against Drug-Resistant Streptococcus iniae and Its Protective Effect on Channel Catfish (Ictalurus punctatus) - Yin, Lizi; Liang, Chao; Wei, Wenyan; Huang, Shuanghui; Ren, Yongqiang; Geng, Yi; Huang, Xiaoli; Chen, Defang; Guo, Hongrui; Fang, Jing; Deng, Huidan; Lai, Weimin; et al. (Frontiers in Microbiology, 2022)
Streptococcus iniae is a zoonotic pathogen, which seriously threatens aquaculture and human health worldwide. Antibiotics are the preferred way to treat S. iniae infection. However, the unreasonable use of antibiotics leads to the enhancement of bacterial resistance, which is not conducive to the prevention and treatment of this disease. Therefore, it is urgent to find new efficient and environmentally friendly antibacterial agents to replace traditional antibiotics. In this study, the antibacterial activity and potential mechanism of thymol against S. iniae were evaluated by electron microscopy, lactate dehydrogenase, DNA and protein leakage and transcriptomic analysis. Thymol exhibited potent antibacterial activity against S. iniae in vitro, and the MIC and MBC were 128 and 256 μg/mL, respectively. SEM and TEM images showed that the cell membrane and cell wall were damaged, and the cells were abnormally enlarged and divided. 2MIC thymol disrupted the integrity of cell walls and membranes, resulting in the release of intracellular macromolecules including nucleotides, proteins and inorganic ions. The results of transcriptomic analysis indicated that thymol interfered with energy metabolism and membrane transport, affected DNA replication, repair and transcription in S. iniae. In vivo studies showed that thymol had a protective effect on experimental S. iniae infection in channel catfish. It could reduce the cumulative mortality of channel catfish and the number of S. iniae colonization in tissues, and increase the activities of non-specific immune enzymes in serum, including catalase, superoxide dismutase, lysozyme and acid phosphatase. Taken together, these findings suggested that thymol may be a candidate plant agent to replace traditional antibiotics for the prevention and treatment of S. iniae infection.